1997
DOI: 10.1007/s001070050219
|View full text |Cite
|
Sign up to set email alerts
|

Einfluß der Verkernung und des Baumalters auf die Eigenschaften von Spanplatten aus Kiefernholz (Pinus sylvestris) Teil 1: Kernholz und seine Eigenschaften

Abstract: Die Eigenschaften yon Spanplatten werden vorwiegend dutch die Eigenschaften der eingesetzten Rohstoffe Holz und Bindemittel sowie dutch die Wechselwirkung zwischen ihnen bestimmt. Ziel eines Forschungsvorhabens war es, die natfirliche Dauerhaftigkeit des Kernholzes der in der Bundesrepublik Deutschland vorkommenden extraktstoffreichen Baumarten Kiefer, Douglasie, L/irche und Eiche bei der Herstellung von Spanplatten mit hoher biotogischer Resistenz gegenfiber holzzerst/Srenden Pilzen zu nutzen. Innerhalb diese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…A similar trend was also reported in a review by Dix and Roffael (1997), who determined lower pinosylvin concentrations in the inner heartwood. Venäläinen et al .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A similar trend was also reported in a review by Dix and Roffael (1997), who determined lower pinosylvin concentrations in the inner heartwood. Venäläinen et al .…”
Section: Resultssupporting
confidence: 89%
“…A similar trend was also reported in a review by Dix and Roffael (1997), who determined lower pinosylvin concentrations in the inner heartwood. Venäläinen et al (2003), however, found no difference in the total amount of extractives between inner and outer heartwood, but the amount of stilbenes (pinosylvin and pinosylvin monomethyl ether) in the inner heartwood was also lower when compared with the outer heartwood.…”
Section: Resultssupporting
confidence: 89%
“…That study ignored the influence of wood extractives (nonstructural phytochemicals) that might directly generate CH 2 O, catalyze lignin to do so, or reduce emissions by reacting with CH 2 O. ,− Schäfer and Roffael’s data suggested a catalytic role of wood extractives in CH 2 O generation; a discussion of that possibility appeared elsewhere . In this study, wood from P. virginiana , P. radiata , and Liriodendron tulipifera was studied with respect to the impact of extractives removal on CH 2 O generation during heating (200 °C, 10 min).…”
Section: Introductionmentioning
confidence: 96%
“…All organic wood components are capable of generating CH 2 O, but lignin appears to be the major source. , Wood extractives are not addressed here, but it is known that the extractives can directly generate CH 2 O, or they may catalyze CH 2 O generation, or they react with CH 2 O such that emissions are reduced. Excluding extractives, this is a study of Virginia pine (Pinus virginiana) to determine the CH 2 O generation potential of its structural biopolymers. Specimens were heated at 200 °C for 10 or 60 min, where the 10 min treatment crudely simulates industrial hot-press conditions.…”
Section: Introductionmentioning
confidence: 99%